2018
DOI: 10.1097/ccm.0000000000002876
|View full text |Cite
|
Sign up to set email alerts
|

The Present State of Neurointensivist Training in the United States: A Comparison to Other Critical Care Training Programs

Abstract: The United Council for Neurologic Subspecialties has developed a directed program development strategy to emulate American College of Graduate Medical Education standards with the goal to have standards that are similar or identical to American College of Graduate Medical Education standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Social awareness about patient safety has also increased the awareness about high-quality neurocritical care among patients and neurologists. Having a neurointensivist staff member and organizing the intensive care unit (ICU) infrastructure are crucially important for providing adequate care to neurocritically ill patients 78. However, there is currently a lack of full-time neurointensivists in Korean hospitals despite the presence of neurological, neurosurgical, or general ICUs in most general hospitals 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social awareness about patient safety has also increased the awareness about high-quality neurocritical care among patients and neurologists. Having a neurointensivist staff member and organizing the intensive care unit (ICU) infrastructure are crucially important for providing adequate care to neurocritically ill patients 78. However, there is currently a lack of full-time neurointensivists in Korean hospitals despite the presence of neurological, neurosurgical, or general ICUs in most general hospitals 9.…”
Section: Introductionmentioning
confidence: 99%
“…Having a neurointensivist staff member and organizing the intensive care unit (ICU) infrastructure are crucially important for providing adequate care to neurocritically ill patients. 7,8 However, there is currently a lack of full-time neurointensivists in Korean hospitals despite the presence of neurological, neurosurgical, or general ICUs in most general hospitals. 9 To our knowledge, the effects of full-time neurointensivist staffing in a dedicated neurological intensive care unit (NRICU)-which may comprise a different patient population than a neurosurgical ICU, a combined neurological and neuro-JCN surgical ICU, or a general ICU-on the quality of care and outcomes of neurocritically ill patients have not been described previously.…”
Section: Introductionmentioning
confidence: 99%
“…One hundred five studies of 657 articles (16%) identified by date and keywords criteria search met inclusion criteria for analysis (Fig. 1) (2, 13–116) and were published in 55 different journals ( Supplemental Table 4 , http://links.lww.com/CCM/H371). Notably, 70 (67%) of the included studies were published in only four journals ( Critical Care Medicine , Journal of Critical Care , Journal of Intensive Care , and Neurocritical Care ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the rapid modernization and development of specialized neurocritical care units and staffed by a subspecialty trained population of neurointensivists and staff [207][208][209], the medical management of cerebral edema developed within this clinical practice is independent of targeting the underlying cellular and molecular mechanisms that drive it [7]. As a result, the nontargeted therapies that are employed in-practice remain the standard of clinical practice [60] and focus on the downstream effects of cerebral edema formation without modulation of the neuroinflammatory cascade that is paramount in all neuronal injury [29,210,211].…”
Section: Discussionmentioning
confidence: 99%